2020
DOI: 10.21608/mjmr.2022.220854
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of ultrasound guided regional block in laparoscopic cholecystectomy

Abstract: Mohamed et al., 150Analgesic effect of ultrasound guided regional block in laparoscopic cholecystectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Also, Mohamed et al reported insignificant statistical differences in the me MAP and HR intraoperatively between the ESPB and QLPB groups. 9,11,12,13 According to our results, postoperative VAS measurements at 15 min, 30 min, and 12 h were significantly reduced in the PVPB group than in the ESPB group and QL3 group. They were significantly greater in the PVPB group than the ESPB group and QL3 group at 6 h postoperatively, with insignificant variations across the 3 groups at 2 and 24 h. Postoperative VAS measurements always were insignificantly different between the ESPB group and QL3 group.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Also, Mohamed et al reported insignificant statistical differences in the me MAP and HR intraoperatively between the ESPB and QLPB groups. 9,11,12,13 According to our results, postoperative VAS measurements at 15 min, 30 min, and 12 h were significantly reduced in the PVPB group than in the ESPB group and QL3 group. They were significantly greater in the PVPB group than the ESPB group and QL3 group at 6 h postoperatively, with insignificant variations across the 3 groups at 2 and 24 h. Postoperative VAS measurements always were insignificantly different between the ESPB group and QL3 group.…”
Section: Discussionsupporting
confidence: 54%
“…14 Moreover, Mohamed et al found that the postoperative VAS measurements were insignificantly different between ESPB and QL3 groups. 12 The previous changes detected in pain perception were reflected in the postoperative hemodynamic changes (MAP and HR). The postoperative MAP and HR measurements at 0 and 12 h were significantly lower in the PVPB group than the ESPB group and QL3group, due to the good analgesia of PVPB as mentioned before.…”
Section: Discussionmentioning
confidence: 99%